Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00216-011-5285-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of isoniazid in biological samples by cation-selective exhaustive injection–sweeping–micellar electrokinetic chromatography

Abstract: Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, infects approximately one third of the current world population. Isoniazid is one of the most frequently used first-line anti-TB drugs. In this study, we developed a sensitive cation-selective exhaustive injection-sweeping-micellar electrokinetic chromatography method (CSEI-Sweep-MEKC) for analyzing isoniazid in human plasma. Parameters including acetonitrile (ACN) percentage in the separation buffer; the injection time, and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Thus, tobacco‐specific N ‐nitrosamines in human urine , methadone and its metabolites in serum from heroin addicts , and isoniazid in patient plasma were successfully determined at picogram per milliliter levels thanks to the increased enrichment factors obtained (6000‐ to 15 000‐fold in some cases ). In general, an effective SPE or liquid–liquid extraction procedure is additionally used to improve the determination of the analytes in these complex biological matrices. Li et al used the CSEI‐sweeping approach to determine cypromazine and its metabolite melamine at picogram per milliliter levels in dairy products.…”
Section: Online Sample Concentration Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, tobacco‐specific N ‐nitrosamines in human urine , methadone and its metabolites in serum from heroin addicts , and isoniazid in patient plasma were successfully determined at picogram per milliliter levels thanks to the increased enrichment factors obtained (6000‐ to 15 000‐fold in some cases ). In general, an effective SPE or liquid–liquid extraction procedure is additionally used to improve the determination of the analytes in these complex biological matrices. Li et al used the CSEI‐sweeping approach to determine cypromazine and its metabolite melamine at picogram per milliliter levels in dairy products.…”
Section: Online Sample Concentration Techniquesmentioning
confidence: 99%
“…As in the previous review, CSEI‐sweeping has been exploited to a greater extent than ASEI‐sweeping and its applications have focused on the determination of drugs and their metabolites in biological samples. Thus, tobacco‐specific N ‐nitrosamines in human urine , methadone and its metabolites in serum from heroin addicts , and isoniazid in patient plasma were successfully determined at picogram per milliliter levels thanks to the increased enrichment factors obtained (6000‐ to 15 000‐fold in some cases ). In general, an effective SPE or liquid–liquid extraction procedure is additionally used to improve the determination of the analytes in these complex biological matrices.…”
Section: Online Sample Concentration Techniquesmentioning
confidence: 99%
“…It was suggested that the higher the S‐β‐CD concentration, the higher the sweeping power. In theory, a high sweeping power could improve the enhancement efficiency during sweeping procedure . Seen from Table , it could be found that resolutions and migration times gradually increased with the stepwise increase in the concentration of S‐β‐CD from 5 to 30 mg/mL, which is mainly caused by the increased interactions between S‐β‐CD and enantiomers.…”
Section: Resultsmentioning
confidence: 96%
“…In the last two years, most applications featuring sequential stacking approaches with sweeping were performed for biochemical components and food/food contaminants. Popularly used was CSEI‐sweeping . Other sequential stacking techniques employed were anion‐selective exhaustive injection (ASEI)‐sweeping , dynamic pH junction‐sweeping , LVSS‐sweeping , t‐ITP‐sweeping , sweeping‐MSS .…”
Section: Sequential Stacking Methodsmentioning
confidence: 99%